Spirituality and Religiosity in Elderly Adults with Chronic Disease - Isabel Patricia Gómez Palencia; Dina Cantillo Banquett; Melisa Coronado Quintana; Arlys López Villamizar; Yecica Vergara Mendoza
Objective.This work sought to explore the relationship between spirituality and religiosity in elderly adults with chronic disease. Methods. This was a cross-sectional cohort study with a representative sample of 229 elderly adults with chronic disease registered in 12 life centers in the city of Cartagena. Reed's Spiritual Perspective and Francis' Religiosity scales were applied. Results. Mean age was 74.4 years, 62.9% were women, and the most frequent occupations were: unemployed (45.9%) and housewives (44.5%); the religion most practiced was Catholicism (81.2%). Levels of spirituality and religiosity were high, showing a moderate and direct correlation (r = 0.57). Conclusion. A directly proportional relationship exists between spirituality and religiosity in elderly adults with chronic disease.